Antifungal activity and inhibitory mechanisms of ferulic acid against the growth of Fusarium graminearum. (April 2023) - Yan, Han; Meng, Xiangyi; Lin, Xianfeng; Duan, Nuo; Wang, Zhouping; Wu, Shijia
Abstract: Fusarium graminearum is a pathogen that can infect wheat, corn and other grain crops, resulting in a reduction in grain yield and nutritional value and even causing serious harm to public health. Ferulic acid (FA) is popularly extracted from a variety of traditional Chinese medicines, such as ferula, asafoetida and angelica, and is a promising fungicide for the preservation of foods due to its antibacterial, antioxidant and anti-inflammatory functions. Based on its efficacy, the inhibitory activity of FA against F. graminearum was evaluated and the involved mechanism was investigated as well. The EC50 and EC90 values were approximately 20 μg/mL and 100 μg/mL, respectively, according to the mycelial dry weight test. TEM and SEM analyses after FA treatment revealed that the cell membrane of hyphae was impaired and showed the following characteristics: coarse surface with wrinkles, blurry ultrastructure edges, and cytoplasmic leakage. In addition, cell integrity and permeability analyses were performed to identify its antifungal mechanism. After FA treatment, the fluorescence intensity of mycelia after PI staining increased significantly (p < 0.001), and the high concentration group showed a continuous rise in extracellular relative conductivity and more significant leakage of nucleic acids and protein. Moreover, FA inhibited ergosterol synthesis in the F. graminearum cell membrane, which confirmed that the target site of FA antifungal action was the cell membrane. Highlights: FA exhibited antifungal effect on Fusarium graminearum. FA induced the disruption of cell surface morphology and internal structure. FA damaged the cell integrity and caused the leakage of cellular content. The cell membrane as the targeted site for the antifungal mechanism of FA.